The Association Between Area Deprivation Index and Patient-Reported Outcomes in Patients with Advanced Cancer (Mary Ann Liebert, 2021)
Background: This analysis describes associations between area deprivation and patient-reported outcomes among patients with advanced cancer. Methods: This is a cross-sectional analysis of baseline data from a multisite primary palliative care intervention trial. Participants were adult patients with advanced cancer. Patient-level area deprivation scores were calculated using the Area Deprivation Index (ADI). Quality of life and symptom burden were measured. Uni- and multivariate regressions estimated associations between area deprivation and outcomes of interest. Results: Among 672 patients, ?0.5 (54%) were women and most (94%) were Caucasian. Mean age was 69.3?10.2 years. Lung (36%), breast (13%), and colon (10%) were the most common malignancies. Mean ADI was 64.0, scale of 1 (low)?100 (high). In unadjusted univariate analysis, Functional Assessment of Cancer Therapy?Palliative (p=0.002), Edmonton Symptom Assessment Scale (p=0.025) and the Hospital Anxiety and Depression Scale anxiety (p=0.003) and depression (p=0.029) scores were significantly associated with residence in more deprived areas (p=0.003). In multivariate analysis, controlling for patient-level factors, living in more deprived areas was associated with more anxiety (p=0.019). Conclusion: Higher ADI was associated with higher levels of anxiety among patients with advanced cancer. Geographic information could assist clinicians with providing geographically influenced social support strategies.